Southwest Research-Extension Center Field Day 1994 (Kansas Agricultural Experiment Station Research Reports, 1994)
Each Field Day report consists of individual research reports on topics specific to the region, including cultural methods for most of the major crops grown in Kansas, mitigating the effects of weeds, insects, and disease associated with those crops, and irrigation. Research is conducted and reports written by staff of the K-State Research and Extension Southwest Research Extension Center.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station); 712; Kansas Agricultural Experiment Station contribution; no. 95-12-S; Kansas; Weather; Crops; Tillage systems; Water management; Weeds; Insect biology and control